DETERMINAN STATUS KEMISKINAN ANAK PADA RUMAH TANGGA KRT PEREMPUAN DI PROVINSI BENGKULU 2018 - Karina Nur Fadila; Agung Priyo Utomo (Seminar Nasional Official Statistics, 2020)
Child poverty is a serious problem. One of the factors that affect it is the sex of the headed-household. Children with female-headed households tend to be more at risk of poverty than children with male-headed households. This is caused by the social assumption that women are a second class society so in the world of work, they don’t have the same opportunities as men. Bengkulu Province was a province in the western region of Indonesia with the highest child poverty rate in 2016 so that it becomes the focus of this study, whereas this study aims to determine the general picture, identify the factors that affect, and analyze the tendency of independent variables on the poverty status of children with female headed-household in Bengkulu Province in 2018. The data used in this study is the results from the practical work of Politeknik Statistika STIS students in 2018. Using the binary logistic regression analysis method, it’s known that the education of household heads, employment status of household heads, number of household members, and marital status of household heads have significant effect on child poverty with female-headed household in Bengkulu Province in 2018. The tendency is greater for children with the highest education of household heads are under senior high school, household heads work in the agricultural sector, have a large number of household members, and the marital status is marriage.